The gender and breeding initiative - Thiele, Graham (International Potato Center, 2017)
Presented by Graham Thiele (RTB / CIP) as part of the 'gender in breeding session' of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017